Selective Embolization Is Safe and Effective for Total Knee Arthroplasty-Associated Recurrent Hemarthroses: A Systematic Review and Meta-Analysis - Sundaram, Kavin; Arnold, Nicholas R.; Mont, Michael A.; Sodhi, Nipun; Warren, Jared; Kamath, Atul F.; Piuzzi, Nicolas S. (The Journal of Knee Surgery, 2019)
Total knee arthroplasty (TKA)-associated hemarthroses are infrequent and often respond to nonoperative therapy. Geniculate artery embolization may provide symptomatic relief in cases recalcitrant to needle aspiration, although no meta-analysis exists regarding this therapy. This meta-analysis aims to assess the rate of symptom relief, the number of embolizations needed to achieve relief, and the rate of complications associated with embolization. Public databases were queried from 1998 until 2018 for TKA-associated recurrent hemarthroses treated with embolization. Eight studies met inclusion and exclusion criteria. Major complications were defined as those requiring readmission or nonelective reoperation; minor complications were defined as those not requiring readmission or reoperation. Pooled statistics were calculated utilizing the method of inverse variance. Fifty-nine patients with a mean follow-up of 30 months (range, 1–50 months) were evaluated. The pooled proportion of patients with symptom improvement following embolization was 86% (95% confidence interval [CI]: 74–93%, I2: 0%, p = 0.97). The average number of embolization procedures was 1.30 (95% CI: 1.03–1.63, I2: 0%, p = 0.66). The pooled proportion of patients who required a second embolization procedure was 26% (95% CI: 15–40%, I2: 0%, p = 0.43), while those requiring three or more procedures was 13% (95% CI: 6–25%, I2: 0%, p = 0.87). The rate of complications were as follows: any complication – 19% (95% CI: 11–32%, I2: 0%, p = 0.81); major complications–8% (95% CI: 3–19%, I2: 0%, p = 0.96); minor complications–18% (95% CI: 10–31%, I2: 0%, p = 0.79); inguinal hematoma–9% (95% CI: 4–19%, I2: 0%, p = 1.00); skin necrosis–15% (95% CI: 7–29%, I2: 0%, p = 0.62); and incision breakdown–7% (95% CI: 3–17%, I2: 0%, p = 1.00). Previous literature on selective artery embolization following TKA is relatively limited. This meta-analysis supports embolization as a potentially safe and effective treatment for recurrent hemarthroses after TKA. Other correctable causes of recurrent hemarthrosis, such as instability or malalignment, must be diligently ruled out prior to utilizing embolization. Surgeons should be aware of embolization's potential role in the postoperative period following TKA.
Keywords: total knee replacement; hemarthrosis; embolization